Kajian Etnomusikologis terhadap Fungsi Sosial dan Budaya Sigu lewuö pada Masyarakat Nias - Hubari Gulo; Yeni Cecilia Fa’omasi Hulu; Agnesti Sinaga (Program Studi Etnomusikologi, Fakultas Ilmu Budaya, Universitas Mulawarman, 2026)
This study examines the social and cultural functions of sigu lewuö, a traditional bamboo flute of the Nias community, through an ethnomusicological approach. The research was conducted in Gunungsitoli and South Nias using qualitative methods, including observation, in-depth interviews with local musicians and community leaders, and literature review. The findings reveal that sigu lewuö has experienced a significant transformation in both meaning and function within contemporary Nias society. Originally associated with mourning rituals and ceremonial contexts, the instrument is now widely used as a medium of entertainment, artistic performance, and cultural preservation. In addition, sigu lewuö serves as an accompaniment to traditional songs, a form of artistic expression, and a symbol of ethnic identity among younger generations. This transformation reflects the adaptive strategies of the Nias community in maintaining and revitalizing traditional cultural practices amid ongoing social, cultural, and technological changes.